Theme Prevalence and Co-Occurrence in Managerial Perceptions of AI Integration in Physical Retail: A Descriptive Qualitative Content Analysis - Kolar, Nina; Pisnik, Aleksandra (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The integration of artificial intelligence (AI) is increasingly shaping the transformation of physical retail, yet managerial perceptions of this process remain underexplored. This study investigates these perceptions through six semi-structured interviews across diverse retail sectors. Utilizing the MAXQDA software for qualitative content analysis, the research identifies key themes: implementation challenges, strategic benefits, required competencies, and human–technology interaction. Co-occurrence analysis reveals a critical tension between technological efficiency and human empathy. Findings indicate that while AI offers operational gains, its success is hindered by technological inadequacies and demographic hesitation. Results suggest that effective adoption depends on balancing automation with "hybrid intelligence" and proactive upskilling to maintain the relational value of physical stores. This research provides localized, practitioner-based insights into the socio-technical complexities of the evolving "phygital" retail landscape.